Educating teachers for moral, civic and citizenship education: Challenges ahead - Chang, L.H. (2005)

(untitled)
Like any other formal subjects such as History or Mathematics, both Moral Education and Civic and Citizenship Education subjects have set or structured curriculum aims, objectives and content. These subjects would thus need teachers who have professional knowledge and expertise to conduct the most appropriate instructions and guidance in learning the subjects This paper will focus on the pre-service programme conducted at University of Malaya and the in-service orientation conducted by the Ministry of Education on educating teachers for teaching Moral Education that would have some implications to educating teachers for teaching Civic and Citizenship Education. However, due to lack of specialist teachers in Moral Education method, many teachers who have not received any form of pre-service and in-service training on Moral Education are in reality teaching the subjects in schools. Given the reality of this situation in schools, this presentation will discuss some challenges pertaining to expanding and enhancing educating teachers for moral, civic and citizenship education.